2(x-4)=4x+3+6

Simple and best practice solution for 2(x-4)=4x+3+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-4)=4x+3+6 equation:



2(x-4)=4x+3+6
We move all terms to the left:
2(x-4)-(4x+3+6)=0
We add all the numbers together, and all the variables
2(x-4)-(4x+9)=0
We multiply parentheses
2x-(4x+9)-8=0
We get rid of parentheses
2x-4x-9-8=0
We add all the numbers together, and all the variables
-2x-17=0
We move all terms containing x to the left, all other terms to the right
-2x=17
x=17/-2
x=-8+1/2

See similar equations:

| 2+4x-10+6x=2(5x-4) | | R^2+8t+16=45 | | 14=b/13 | | 5x+-6+3x=10 | | Y=-8x-24 | | -10a+11=-149 | | (2x-7)(3x+8)=0 | | 3x+13=2x-2 | | 0.8x^2-10x=0 | | 64•w=5568 | | 18-4b=6 | | w/3+-7=-4 | | (x^2-3x)(x^2-3x+2)=0 | | 1.12+2.5x=2.7x+0.7 | | 1/4x-4x=3/2x+3/4 | | 4^x+2=16^x-9 | | 19=-3-2n | | r/2+5=8 | | -22(3x-10)+8x=7x+20+7x | | X/72=18/x | | k/2+7=10 | | 24=6x-3 | | x+57=40 | | x/2+-1=0 | | 8x+10=3x-90 | | (x^2-5x-16)^4/3=0 | | 22-5(6v-1)=-64F | | 13=3t-5 | | -3x+12-9x+8=-3(4x+7) | | 8•x•55=-(8•x•55) | | (.6)x=205 | | x*2.5=x+0.5 |

Equations solver categories